HUBUNGAN ANTARA KESEPIAN DAN KECENDERUNGAN NARSISISTIK PADA PENGGUNA JEJARING SOSIAL MEDIA INSTAGRAM - Sembiring, Kembaren Dianelia Reginanta (Faculty of Psychology, Diponegoro University, 2017)
This study aims to investigate the relationship between loneliness and narcissistic tendencies on social network Instagram users. The population in this study is the users of social network Instagram for at least 6 months, aged 18-24 years, has a minimum of 90 photos on their instagram account, actively access instagram accountÂ for once until twice a day. Snowball sampling is used in this study, with the participation of 65 participants. Measurement instrument used in this study were UCLA Loneliness Scale Version 3 and the Narcissistic Personality Inventory 40 Items. Pearson's Product Moment is used to test the correlation between loneliness and narcissistic tendency. The results of this study showed that there was no relationship between loneliness and narcissistic tendency among social network Instagram users (r = -0.080, p=.264).